Water Spectra in the Region 4200–6250 cm-1, Extended Analysis of v1+v2, v2+v3, and 3v2 Bands and Confirmation of Highly Excited States from Flame Spectra and from Atmospheric Long-Path Observations; Journal of Molecular Spectroscopy; Vol. 213, № 2 - Mikhailenko S. N. Semen Nikolaevich; Tyuterev V. G.; Starikov V. I.; Albert K. K.; Winnewisser B. P.; Winnewisser M.; Mellau G.; Camy-Peyret C.; Lanquetin R.; Flaud J. M.; Brault J. W. (2002, 2002)
Title screen